Anti‐FIRΔexon2 autoantibody as a novel indicator for better overall survival in gastric cancer. Issue 2 (2nd January 2021) - Kobayashi, Sohei; Hiwasa, Takaki; Ishige, Takayuki; Kano, Masayuki; Hoshino, Tyuji; Rahmutulla, Bahityar; Seimiya, Masanori; Shimada, Hideaki; Nomura, Fumio; Matsubara, Hisahiro; Matsushita, Kazuyuki
Abstract: There is no clinically available biomarker for efficiently indicating the overall survival or therapy response of gastric cancer (GC). The autoantibodies (Abs) in the sera of anti‐far‐upstream element‐binding protein‐interacting repressor‐lacking exon2 (FIRΔexon2), anti‐sorting nexin 15, and anti‐spermatogenesis and oogenesis–specific basic helix–loop–helix 1 were markedly higher in GC patients than in healthy donors (HDs). These Abs were identified by large‐scale serological identification of antigens by recombinant cDNA expression cloning screenings and their expression levels were evaluated by amplified luminescence proximity homogeneous assay. In particular, compared with age‐matched HDs, the level of anti‐FIRΔexon2 Abs in GC patients was significantly higher ( P < .001). The Spearman's rank correlation analysis between anti‐FIRΔexon2 Abs and clinically available tumor markers such as carcinoembryonic antigen (CEA) was statistically insignificant, indicating that FIRΔexon2 Abs is an independent biomarker. We performed receiver‐operating curve analysis to evaluate the anti‐FIRΔexon2 Ab as a candidate biomarker with CEA and carbohydrate antigen 19‐9 (CA19‐9). The overall survival of GC patients with high anti‐FIRΔexon2 Abs titer was significantly favorable ( P = .04) than that of GC patients who were below detection level of anti‐FIRΔexon2 Abs. However, clinical stages were not apparently correlated with the levels of anti‐FIRΔexon2 Ab, CEA, and CA19‐9. In conclusion, anti‐FIRΔexon2 Abs detected in GC patients is a potential biomarker for monitoring a better prognosis. Hence, anti‐FIRΔexon2 Abs is a promising biomarker for indicating better overall survival of gastric cancer patients. Abstract : Anti‐FIRΔexon2 Ab is a predictive or overall survival marker for patients with gastric cancer.